2015
DOI: 10.1177/0894439315587258
|View full text |Cite
|
Sign up to set email alerts
|

Using Paradata to Predict and Correct for Panel Attrition

Abstract: This article addresses the questions of whether paradata can help us to improve the models of panel attrition and whether paradata can improve the effectiveness of propensity score weights with respect to reducing attrition biases. The main advantage of paradata is that it is collected as a byproduct of the survey process. However, it is still an open question which paradata can be used to model attrition and to what extent these paradata are correlated with the variables of interest. Our analysis used data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 51 publications
0
29
0
1
Order By: Relevance
“…The authors in this case found that careless answering patters were related to educational attainment, employment income, a greater likelihood of being employed in a high-skilled job, and self-reported measures of conscientiousness, even after controlling for cognitive ability. Other work in the area of survey research has also found that non response, inconsistent response patterns, and the amount of time respondents spend answering individual items are an indicator of respondent's conscientiousness (See,Jensen & Soland, 2016;Roβmann & Gummer, 2016;Segal, 2012).…”
mentioning
confidence: 99%
“…The authors in this case found that careless answering patters were related to educational attainment, employment income, a greater likelihood of being employed in a high-skilled job, and self-reported measures of conscientiousness, even after controlling for cognitive ability. Other work in the area of survey research has also found that non response, inconsistent response patterns, and the amount of time respondents spend answering individual items are an indicator of respondent's conscientiousness (See,Jensen & Soland, 2016;Roβmann & Gummer, 2016;Segal, 2012).…”
mentioning
confidence: 99%
“…We chose a specific focus on surveys and digital trace data for this special issue. This excludes the combination of survey data with, for example, paradata (e.g., Roßmann & Gummer, 2015), geo data (e.g., Schweers, Kinder-Kurlanda, Müller, & Siegers, 2016), administrative records (e.g., Schnell, 2014), eye tracking (e.g., Vraga, Bode, & Troller-Renfree, 2016), or traditional forms of media content such as television or newspaper coverage (for a review, see de .…”
Section: Linking Surveys and Digital Trace Data: Ways Of Linking And mentioning
confidence: 99%
“…For example, as Kreuter and Olson (2013) summarize, a wealth of studies have examined call records, contact history, and time to completion in studying nonresponse in other modes. However, only a handful of studies (e.g., Crawford, Couper, & Lamias, 2001;Sauermann & Roach, 2013) have investigated similar information for web surveys or utilized prior survey paradata to understand nonresponse in a panel setting (McLauchlan & Schonlau, 2016;Roßmann & Gummer, 2016).…”
Section: Framework For Categorizing Paradatamentioning
confidence: 99%